2020
DOI: 10.1371/journal.pone.0233750
|View full text |Cite
|
Sign up to set email alerts
|

PFKP is transcriptionally repressed by BRCA1/ZBRK1 and predicts prognosis in breast cancer

Abstract: ObjectivesThe present study aims to elucidate the underlying mechanism how PFKP is regulated by BRCA1 and the clinical significance of PFKP in breast cancer. MethodsMEF-BRCA1 4/4 and the wild type counterpart MEF-BRCA1 +/+ cell lines were used to test the sensitivity of glucose depletion in culture medium. Glucose Assay Kit was used to quantify glucose levels in cultural supernatant and cell lysate. Real time PCR was used to measure the mRNA expression levels of genes. Western blot was used to detect protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…However, further experiments were needed to explore how high PFKP expression improves outcomes in ccRCC patients, which was not consistent with other studies in other types of cancer. 10,12,36 In any case, we provided a newly exciting insight into understanding the role of PFKP in ccRCC.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, further experiments were needed to explore how high PFKP expression improves outcomes in ccRCC patients, which was not consistent with other studies in other types of cancer. 10,12,36 In any case, we provided a newly exciting insight into understanding the role of PFKP in ccRCC.…”
Section: Discussionmentioning
confidence: 95%
“…34,35 Shen et al 10 found that PFKP regulated the level of glycolysis in lung cancer and was associated with tumor size, proliferation, and patient prognosis. PFKP also has been demonstrated to increase the risk of poor prognosis in breast cancer patients 36 and promote the malignant proliferation of OSCC. 9 Meanwhile, it was noteworthy that the high expression of PFKP was considerably associated with a good prognosis in ccRCC patients.…”
mentioning
confidence: 99%
“…PFKP is up-regulated in lung cancer and regulates glucose metabolism [ 31 ]. It is a prognostic marker in breast cancer [ 32 ]. LATS2 encodes a serine/threonine protein kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two additional ZBRK1 target genes, which are implicated in cellular metabolism, were found to be directly bound and repressed by ZBRK1/BRCA1 transcriptional repressor complex: Phosphofructokinase P ( PFKP ) [ 93 ] and Glutamate-oxaloacetate Transaminase 2 ( GOT2 ) [ 94 ]. Both genes were shown overexpressed in BRCA, causing glycolysis dysregulation and increased aspartate metabolism, respectively.…”
Section: Krab-zfps Roles In Cancer Cellsmentioning
confidence: 99%
“…Both genes were shown overexpressed in BRCA, causing glycolysis dysregulation and increased aspartate metabolism, respectively. Reduced ZBRK1/BRCA1 activity on their promoters resulted in PFKP and GOT2 upregulation, which was associated with adverse outcomes in BRCA patients [ 93 , 94 ]. BRCA1/ZBRK1 duet was shown as well to interact with another transcriptional co-repressor, namely CtBP-interacting protein (CtIP).…”
Section: Krab-zfps Roles In Cancer Cellsmentioning
confidence: 99%